2020
DOI: 10.3390/s20030705
|View full text |Cite
|
Sign up to set email alerts
|

Bifocal Ultrasound Focusing Using Bi-Fresnel Zone Plate Lenses

Abstract: In this work, we present a bifocal Fresnel zone plate (BiFZP) capable of generating focusing profiles with two different foci. The performance of the BiFZP is demonstrated in the ultrasound domain, with a very good agreement between the experimental measurements and the finite element method (FEM) simulations. This lens becomes an appealing alternative to other dual-focusing lenses, in which the foci location can only be set at a limited range of positions, such as M-bonacci zone plates. Moreover, the variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Figure 1(b) shows a schematic of the inner BFZP consisting of two Fresnel zone plates (FZPs). The inner FZP with four concentric ring slits has a focal length of f 2 and the outer FZP with four concentric ring slits has a focal length of f 3 [41,42]. As an acoustic plane wave transmits through the BFZP, an axial bifocal acoustic beam (BAB) with two focal points of f 2 and f 3 can be formed.…”
Section: Hybrid Acoustic Artificial Plate For Generating a Three-dime...mentioning
confidence: 99%
“…Figure 1(b) shows a schematic of the inner BFZP consisting of two Fresnel zone plates (FZPs). The inner FZP with four concentric ring slits has a focal length of f 2 and the outer FZP with four concentric ring slits has a focal length of f 3 [41,42]. As an acoustic plane wave transmits through the BFZP, an axial bifocal acoustic beam (BAB) with two focal points of f 2 and f 3 can be formed.…”
Section: Hybrid Acoustic Artificial Plate For Generating a Three-dime...mentioning
confidence: 99%
“…To overcome these disadvantages of phased arrays, studies have investigated methods for controlling the focal length by the operating frequency using a Fresnel zone plate (FZP), in which several rings are arranged concentrically on a plane [15][16][17][18] . For example, Fuster et al measured the sound eld in a water tank after installing metal FZP lenses at a distance of 35 cm from a planar ultrasonic transducer, and they found that the focal length depends almost linearly on the operating frequency 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fuster et al measured the sound eld in a water tank after installing metal FZP lenses at a distance of 35 cm from a planar ultrasonic transducer, and they found that the focal length depends almost linearly on the operating frequency 18 . The disadvantage of an FZP-based acoustic lens [15][16][17][18][19] is that it requires a space between the planar transducer and itself, thus increasing the space between the transducer and tumor. FUS transducers generally operate at high frequencies above 0.8 MHz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the case of Fibonacci sequences, the ratio between both foci is z 2 /z 1 = 1/(ϕ 2 − 1), with ϕ 2 = (1 + √ 5)/2 being the golden mean. Other alternative methods for providing bifocal profiles based on combining preexisting Fresnel ZPs have also been proposed in [28], but they require a complex design process with an accurate control of the phase interference pattern.…”
Section: Introductionmentioning
confidence: 99%